THE SUCCESS OF GAME SHOP OPERARORS IN THAILAND - Singhanate, Porjai; Meksuwan, Atchara; Khamrach , Chiraprapha (Journal of MCU Nakhondhat, 2023)
The objectives of this research were 1) to study the opinion level of special features of the game, player satisfaction, and the success of game shop operators in Thailand, and 2) to study the game's special characteristics and player satisfaction that affected the success of game store operators in Thailand. This is quantitative research. The population was game shop operators in Thailand in 2022, a total of 296 locations, by determining the size of the sample according to Taro Yamane's table. A sample of 171 places was selected by purposive sampling. The tools used for collection were questionnaires which has been inspected for quality by qualified experts. The statistics used to analyze the data were mean, standard deviation, and multiple regression analysis. The research results showed that 1) the sample group mostly was male. Most average age was 25-35 years old with a bachelor's degree. Most of them were in the central regian. The business operation period was 1-5 years. The time when customers came to use the service was found that most of them are 15.00 – 16.00. 2) Special features of the game were game challenges, the engagement, and virtual reality of the game, respectively. 3) Player satisfaction were player reaction and player perception, respectively. While 4) Game shop success were management with understanding, and potential profitable, respectively. In addition, special features of the game and player satisfaction that affected the success of game store operators in Thailand had two predictive variables: player satisfaction and game characteristics, respectively, with an R Square of .693